Digitizing the presidential elections in Iraq: the international and political journal - Al-Zaidi , Prof.Dr Rashid Amara; Omar , Assist lecturer Chanar (The International and Political Journal, 2025)
Information and communication technology (ICT) is the main driving force shaping the 21st century. Its integration into the political realm has had the most significant impact on society, as it has permeated every stage of the electoral process to ensure efficiency, accuracy, and speed. In recent years, elections have been a fertile ground for introducing new technologies, and countries have successfully tested and implemented new voting methods and systems to manage their electoral processes. Iraq is among the countries that have recently started using these technologies in parliamentary elections. Technically, the Iraqi parliamentary elections in 2014, 2018, 2021, and most recently in the provincial council elections in December 2023 have seen the use of technological tools, including biometric applications for voter registration, biometric devices for verifying voter identity on election day, electronic counting machines to expedite results, devices for electronically transmitting election results, and electronic monitoring through surveillance cameras at polling centres and stations. The study results show that the introduction of technology—despite the use of electronic devices in various stages of the Iraqi elections—represents a significant development towards improving the efficiency and transparency of the electoral process. However, several challenges have arisen that have impeded the application of these technologies and ensured electoral conditions, which have led to significant problems from the start of the process to the announcement of results. Examples include malfunctions of voter verification and voting devices, delays in opening some polling stations due to technical issues, and suspicions from political parties and entities regarding election result manipulation both inside and outside Iraq.